A Concurrent Programming Language for Arduino and Educational Robotics - Morán, Ricardo (2017)
Arduino is currently one of the most popular platforms for educational robotics due to its low cost and large amount of available resources online. The Arduino software library provides an abstraction layer over the hardware details, making it possible for novices to build interesting projects. However, its lack of support for concurrency makes some educational robotics projects difficult. In this paper, we explore different approaches to solve this problem and we propose the implementation of a concurrent programming language supported by a virtual machine running on the Arduino board.